The Effect of Curcumex Supplement (Containing Turmeric, Ginger, and Black Pepper Extract) on Clinical Manifestations and Laboratory Findings of Patients with COVID-19 - Roya Ghasemian; Masoud Aliyali; Seyed Hossein Mehravaran; Iradj Maleki; Hossein Mohammadi; Ali Asghar Hemmati; Sara Bayat; Saber Palar; Gholamreza Houshmand (Journal of Mazandaran University of Medical Sciences, 2024)
Background and purpose: Covid-19 is the name of the disease caused by the new SARS-Cov-2 virus. Thus far, numerous non-specific therapies have been employed for this viral infection, however, the majority of these medications have proven to be ineffective and have been correlated with a multitude of adverse effects for patients. Therefore, the use of medicinal plants has received a lot of attention. The current study aims to investigate the effects of the supplemental drug Curcumex on the healing process in outpatients with COVID-19. Materials and methods: The present study, which is a double-blind randomized controlled clinical trial, was conducted on outpatients with covid-19 which has the code of ethics number IR.MAZUMS.REC.1400.593 from Mazandaran University of Medical Sciences. The inclusion criteria for this study include patients who had a ground glass appearance in the CT scan of the chest, the presence of clinical symptoms such as dry cough, shortness of breath, fever, weakness, diarrhea, headache, runny nose, or having a history of contact with a corona patient or recent travel to High-risk areas and people who had a positive PCR result in the nasopharyngeal swab were defined. Curcumex is a new herbal medicine that contains a combination of black pepper, turmeric, and ginger. Black pepper is hot in nature and has astringent, anti-bloating, and digestive properties. Antioxidant and anti-inflammatory effects have been reported for this plant, which can be useful in COVID-19 disease. The sample size was equal to 60 people who were divided into 2 intervention and control groups of 30 people. Both groups received routine medications prescribed for outpatients. In addition to these treatments, one group received curcumex (containing 170 mg of ginger, 4 mg of black pepper, and 340 mg of turmeric) daily, and the control group received a placebo. Results: The results of the current study indicated that the average duration of all clinical symptoms measured in this study was significantly less in the intervention group than in the control group (shortness of breath: 2.13 days vs. 3.66 days; cough: 4 days vs. 7.6 days; Gastrointestinal symptoms: 0.73 days vs. 2.21 days and myalgia: 4.1 days vs. 9.2 days). Also, these results show that the average body temperature before the start of the intervention in the intervention group was 38.32 degrees Celsius and 38.17 degrees Celsius in the control group. This rate 5 day after the start of the study in the intervention group was significantly lower than the control group (37.46 degrees Celsius vs. 37.92). The average oxygen saturation before the intervention was 94.76% in the intervention group and 95.63% in the control group. This amount 5 day after the start of the study in the intervention group was significantly higher than the control group (97.16% vs. 96.1%) (Table 2). to the control group. The results of this study showed that the average number of lymphocytes after the intervention in the intervention group increased significantly compared to the control group (1544.46 in the intervention group and 1132.58 in the control group). Conclusion: This study showed that daily consumption of Curcumex drug as a supplement along with other routine treatments of COVID-19 disease has a positive effect on the recovery process of the disease shortens the course of clinical symptoms, reduces inflammatory markers by a quarter, and corrects lymphopenia. The duration of clinical symptoms, including shortness of breath, cough, myalgia, and gastrointestinal symptoms in patients with COVID-19 who have been treated with Curcomex has significantly decreased. Furthermore, these results indicated that the recovery of fever and hypoxemia (decreased hemoglobin oxygen saturation) in the intervention group was faster than the placebo group and was significantly less than the group of patients who received a placebo.